Impact of Streetscape on the Image of a City: A study and analysis of streetscapes of Delhi, India: Exploring the Relationship Between Streetscape Design and City Image: A Case Study of Delhi, India (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The streets of cities are the connecting elements that make urban life possible. They not onlyallow physical movement but also become vantage points for appreciating the urban environmentincluding but not restricted to architecture alone. From the various tangible and intangible factorsconcerning the streets in an urbanscape, people draw a certain image of the city leading to visual andpsychological associations. In India, streets have been not just a means to connectivity but also venuesto myriad events and activities that affect the users in some way or the other. To understand and analyzewhether or how the streetscape really impacts the image of a city, a survey was conducted with thereference of the streetscapes of two very prominent and commercially set streets of Delhi in IndiaChandni Chowk from Old Delhi and Connaught Place from New Delhi. The survey was conducted in anonline mode due to the pandemic with 107 responding participants last year before the redesignedChandni Chowk was opened for public use. The diverse participants were questioned about differentaspects of streetscape focusing on their preferences and opinions across factors including inclusivity,accessibility, safety, ambience, activities and variety of street elements. The results acquired from thesurvey showed how the elements of the streets, the streetscape design and the image of the city wererelated. Further analysis of the survey results led to conclusions about the preferences of the peopleregarding streetscape and their aspirational requirements concerning the streetscapes of the city.